Penerapan Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar Siswa SMPN 18 Sigi pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) - Hajerina Hajerina (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2017)
This research is a classroom action research with the aim to improve student learning result of SMPN 18 Sigi toward SPLDV. An alternative action used to achieve that goal by applying Contextual Teaching and Learning (CTL) approach which is a learning that relate material to real life situation both in groups and individuals which concists 0f 7 components, namely : (1) Contructivisme, (2) Quistioning, (3) Inquiry, (4) learning community, (5) modelling, (6) reflection, (7) authentic assessment. The subjects of this study were students of class VIII E SMPN 18 Sigi. The design of this study using the model Kemis and Mc Taggart consisting of the planning, action, observasion, and reflection. Based on the results of research shows that the learning activities have been running well and have increased in every cycle. This can be seen from the percentage of classical learning mastery. In the final test of cycle I reached the average student scoe of 72.22 % and in the final test of cycle II increased to 83.33% in good qualification.